Extractives Content and Colour Properties of 11-year-old Perhutani Superior Teakwood from Ngawi Forest Management Unit - Zulkahfi Zulkahfi; Denny Irawati; Tomy Listyanto; Dian Rodiana; Ganis Lukmandaru (Jurnal Ilmu Kehutanan)
The utilization of young teak wood had increased due to the gap in demand and the supply of raw materials. To meet the high demand, Perhutani had planted the fast growing of superior teakwood (Jati Plus Perhutani/JPP). This vegetative reproduction may affect the wood properties. Extractive content is important considering its relationship with the natural durability of wood and colour properties. The purpose of this study was to find out the effect of radial and longitudinal directions on extractives content and colour properties from JPP. The JPP wood samples (11 years) were located in Ngawi Forest Management Unit. The observed factors were vertical (bottom, center, top) and radial (sapwood, outer heartwood, inner heartwood) directions. Wood extracts were obtained by successive extraction (toluene, ethanol, and hot water) in a soxhlet. Total phenolic content was also determined by Folin-Ciocalteu method in toluene soluble extract. Colour properties were determined by CIEL*a*b* system. The result showed that vertical direction had significant effect as the bottom part showed the highest value in ethanol extract content but it had lower value in total phenolic content. Brightness (L*) value was comparatively high at the top part, while redness (a*) value was high at the bottom part. The levels of toluene, ethanol, and total extract content had a significant different between sapwood and heartwood as well as between outer heartwood and inner heartwood. Based on radial direction, the colour was darker in outer heartwood compared to the other parts. The correlation degree between the values of hot water extract and L* was significant (r = -0.72) in sapwood part. In heartwood, the correlation between ethanol, hot water, and total extract contentwith L* values were negative (r = -0.70; -0.52; -0.78, respectively). The correlation between a* value and total phenolic content was moderately significant (r = -0.58). The comparatively low content of extractive compared to mature woods as well as inhomogeneity of colour properties in vertical position should be noticed for young JPP wood utilization.